MULTIAGENT APPROACH TO OPTIMIZATION OF RESOURCE DISTRIBUTION IN LARGE INFORMATION SYSTEMS. - Колумбет, Вадим (SWorldJournal, 2021)
The article considers the tasks of resource allocation in multi-agent systems, options for their applicability and existing methods of solving these problems. The task of resource allocation is one of the fundamental tasks: from the efficient allocation o